Energetic and myocellular pathways in cardiac and skeletal muscle following anthracycline chemotherapy. (3rd October 2022) - Gamble, D; Khan, H; Ross, J; Cheyne, L; Rudd, A; Horgan, G; Hannah, A; Urquhart, G; Masannat, Y; Elsberger, B; Sharma, R; Dawson, D
Abstract: Background: Anthracycline-related cardiac dysfunction is a recognised consequence of cancer therapies. Here we assess resting cardiac and skeletal muscle energic status as an early mechanistic pathway of myocyte derangement and explore molecular targets of skeletal myocyte metabolism, protein synthesis/degradation and mitochondrial biogenesis signalling. Methods: We conducted a prospective, mechanistic, observational, longitudinal study of chemotherapy-naive breast cancer patients undergoing anthracycline-based chemotherapy, compared to a healthy control group. 31P-Magnetic Resonance spectroscopy in cardiac and skeletal muscle (phosphocreatine/gamma adenosine triphosphate (PCr/yATP) and inorganic phosphate/phosphocreatine (Pi/PCr) ratios respectively), cardiac magnetic resonance (CMR) imaging inclusive of T1 and T2 mapping, echocardiography-derived global longitudinal strain function, serum NT-pro-BNP and skeletal muscle biopsies from the right vastus lateralis were assessed before and after 3 cycles of Flurouracil, Epirubicin and Cyclophosphamide followed by 3 cycles of Docetaxel. Statistical significance was set at p<0.05. Results: Twenty-five female breast cancer patients (median age 53 years, range 32–74 years) receiving a mean epirubicin dose 307 mg/m 2 ) and twenty-eight controls (median age 44 years, range 23–65) were recruited. All study assessments in breast cancer patients at pre-chemotherapy stage were comparable to the matched healthy controls. However, following chemotherapy, breast cancer patients demonstrated a small but significant reduction in cardiac function (global longitudinal strain −22.9±3.9 vs −19.1±3.3%, p=0.01 and CMR-derived ejection fraction 65±5 vs 62±4%, p=0.047), a mild increase in CMR-derived indexed left ventricular volumes (end diastolic 65±10 vs 74±11 ml/m 2, p=0.014 and end systolic 23±5 vs 28±5 ml/m 2, p=0.01) as well as an increase in left ventricular T1 and T2-mapping (1289±29 vs 1321±31 ms, p=0.004 and 50±4 vs 55±7 ms, p=0.027, respectively) and serum NT-Pro-BNP (49±25 vs 108±84 pg/m, p=0.008). After epirubicin, there was significant reduction in cardiac PCr/yATP ratio (2.0±0.7 vs 1.2±0.6, p=0.007) and a significant increase in skeletal muscle Pi/PCr ratio (0.13±0.04 vs 0.22±0.2, p=0.008) – Figure 1. Following chemotherapy, there was significant upregulation of skeletal myocyte protein synthesis (mammalian target of rapamycin, 0.44±0.4 vs 0.53±0.2, p<0.001) and degradation (Calcium/calmodulin dependent protein kinase II, 1.4±0.7 vs 2.7±1.1, p<0.001), metabolism (peroxisome proliferator-activated receptor gamma, 0.35±0.2 vs 0.60±0.1, p<0.001) and muscle mass regulator myostatin-2 (0.16±0.1 vs 0.24±0.1, p<0.001). Conclusion: Contemporary doses of epirubicin for breast cancer result in significant reduction of cardiac and skeletal muscle high energy 31P-metabolism alongside skeletal myocellular alterations of protein synthesis and metabolic regulation pathways. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Tenovus ScotlandNHS Grampian Endowment fund